The Troika Host–Pathogen–Extrinsic Factors in Tuberculosis: Modulating Inflammation and Clinical Outcomes - Bastos, Helder Novais; Osório, Nuno S.; Gagneux, Sebastien; Comas, Iñaki; Saraiva, Margarida (Frontiers in Immunology, 2018)
The already enormous burden caused by tuberculosis (TB) will be further aggravated by the association of this disease with modern epidemics, as HIV and diabetes. Furthermore, the increasingly aging population and the wider use of suppressive immune therapies hold the potential to enhance the incidence of TB. New preventive and therapeutic strategies based on recent advances on our understanding of TB are thus needed. In particular, understanding the intricate network of events modulating inflammation in TB will help to build more effective vaccines and host directed therapies to stop TB. This review integrates the impact of host, pathogen and extrinsic factors on inflammation and the almost scientifically unexplored complexity emerging from the interactions between these three factors. We highlight the exciting data showing a contribution of this troika for the clinical outcome of TB and the need of incorporating it when developing novel strategies to rewire the immune response in TB.